Application of the thermal dose concept for predicting the necrosed tissue volume during ultrasound surgery - Damianou, Christakis A.; Hynynen, K.; Fan, X. (My University, 1993)
The concept of calculated thermal dose was used to predict the size of the necrosed tissue volume during high-intensity focussed ultrasound surgery. The model presented was verified using experimental data in rabbit muscle and cat brain. The agreement is good and therefore, this model can be used to give guidelines for the sonication prior to clinical ultrasound surgery.
Keywords: biological effects of acoustic radiation; biomedical ultrasonics; surgery; ultrasonic effects